2019
DOI: 10.1016/j.jaging.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Co-creativity, well-being and agency: A case study analysis of a co-creative arts group for people with dementia

Abstract: At the heart of this paper is an exploration of artistic co-creativity involving people with dementia and their partners. Co-creativity promotes a relational approach to creativity which nurtures inclusion and participation. This paper investigates how co-creativity can affect well-being from the perspectives of people with dementia and their carers; and explores how well-being and agency might be usefully reconsidered. The article draws on findings from a small-scale study ‘With All’ that focused on music and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 33 publications
0
52
3
1
Order By: Relevance
“…Next, no significant moderation effects were found between carer presence and number of sessions attended for wellbeing outcomes. This is at odds with previous findings in this area (Bourne et al, 2019;Isserow, 2008;MacPherson et al, 2009;Zeilig et al, 2019) that suggested being accompanied by a carer was a key component. Whilst the importance of social relationships and the supporting role of informal carers has been established as contributing to subjective wellbeing (Lucas & Dyrenforth, 2006), it may be this is less of a factor in ABI over time.…”
Section: Carer Presencecontrasting
confidence: 60%
See 3 more Smart Citations
“…Next, no significant moderation effects were found between carer presence and number of sessions attended for wellbeing outcomes. This is at odds with previous findings in this area (Bourne et al, 2019;Isserow, 2008;MacPherson et al, 2009;Zeilig et al, 2019) that suggested being accompanied by a carer was a key component. Whilst the importance of social relationships and the supporting role of informal carers has been established as contributing to subjective wellbeing (Lucas & Dyrenforth, 2006), it may be this is less of a factor in ABI over time.…”
Section: Carer Presencecontrasting
confidence: 60%
“…For example, Bourne et al (2019) reported increases in wellbeing for both dyad members following a singing and an art viewing session, with the singing group also demonstrating decreases in self-reported stress. Similarly, in a study using music and dance, increases in wellbeing were also found for both dyad members (Zeilig et al, 2019).…”
Section: Arts-based Interventionsmentioning
confidence: 70%
See 2 more Smart Citations
“…As part of this theme, participants displayed a confidence and independence in being able to direct questions to and challenge each other and share different ideas, which encouraged group collaboration . As outlined by others, this reflects the potential added benefits that can come from the social interactions within the groups ( Zeilig et al ., 2019 ). Research has shown that engaging in activities with others in heritage settings can reduce isolation and provide a sense of “normality” for PLWD and caregivers through taking part in activities in the community as they may have done before the onset of dementia ( Sharma & Lee, 2019 ).…”
Section: Discussionmentioning
confidence: 86%